Risk Factors for Perioperative Respiratory Adverse Events in Children with Recent Upper Respiratory Tract Infection: A Single-Center-Based Retrospective Study - Lee HJ; Woo JH; Cho S; Oh HW; Joo H; Baik HJ (Dove Medical Press, 2020)
Hyun Jung Lee,1 Jae Hee Woo,2 Sooyoung Cho,3 Hye-Won Oh,1 Hyunyoung Joo,3 Hee Jung Baik2 1Department of Anesthesiology and Pain Medicine, Ewha Womans University Seoul Hospital, Seoul, South Korea; 2Department of Anesthesiology and Pain Medicine, College of Medicine, Ewha Womans University, Seoul, South Korea; 3Department of Anesthesiology and Pain Medicine, Ewha Womans University Mokdong Hospital, Seoul, South KoreaCorrespondence: Hee Jung BaikDepartment of Anesthesiology and Pain Medicine, College of Medicine, Ewha Womans University, 25, Magokdong-ro 2-gil, Gangseo-gu, Seoul 07804, Republic of KoreaTel +82-2-2650-2868Fax +82-2-2655-2924Email baikhj@ewha.ac.krPurpose: In pediatric patients, the most common reason for delaying surgical intervention is an upper respiratory tract infection (URI). To date, there has been no consensus regarding the optimal timeframe for deferring surgery in children with URI. We conducted this study to evaluate whether a URI symptom-free period and other risk factors affect the incidence of perioperative respiratory adverse events (RAEs).Patients and Methods: The study population included 267 pediatric patients (aged 0 to 13 years) with a recent URI episode who underwent surgery under general anesthesia. Following a retrospective review of medical records, several risk factors including a URI symptom-free period for intra- and postoperative RAEs were analyzed using univariate and multivariate logistic regression analyses.Results: RAEs occurred in 23 of 267 patients (8.6%). Univariate analysis revealed that abnormal preoperative chest images (odds ratio [OR], 7.48; 95% confidence interval [CI], 2.46– 22.68, p < 0.001) and emergency operations (OR, 2.84; 95% CI, 1.03– 7.81, p = 0.04) were associated with RAEs. Four variables (abnormal preoperative chest images, emergency operations, age under 1 year and symptom-free period of 7– 13 days) with a significance of < 0.20 in the univariate logistic regression analysis were selected as candidate risk factors for the multivariate model. Among the four variables, abnormalities in preoperative chest images (OR, 7.60; 95% CI, 2.28– 25.3, p = 0.001) and a symptom-free period of 7– 13 days (OR, 0.13; 95% CI, 0.02– 0.88, p = 0.04) were independently associated with RAEs in multivariate logistic regression analysis.Conclusion: For pediatric patients who require surgery and have a recent history of URI, procedures should be performed after a URI symptom-free period of at least 1– 2 weeks. Confirming the absence of abnormalities in preoperative chest images can reduce the incidence of perioperative RAEs.Keywords: pediatric, general anesthesia, upper respiratory tract infection, respiratory adverse event